Experimental Study on the Seismic Behaviour of Reinforced Concrete Bridge Piers Strengthened by BFRP Sheets - Yong Li; Meng-Fei Xie; Jing-Bo Liu (Advances in Civil Engineering)
With the continuous development of the ductility capacity concept for seismic design of bridges, the ductility capacity of many existing bridges does not meet the requirements of the current code for seismic performance because of the low reinforcement ratio and reinforcement corrosion of reinforced concrete (RC) piers. Because of their superior mechanical properties and low price, basalt fibre-reinforced polymer (BFRP) sheets have potential application in the seismic retrofits field of existing bridges. To study the seismic strengthening effect of RC pier columns, scaled specimens with standard reinforcement ratios, with low reinforcement ratios according to the past code and with corroded reinforcements, were designed and manufactured and then wrapped and pasted with BFRP sheets on the plastic hinge areas. Pseudostatic tests were conducted to verify the seismic performance of the strengthened and unstrengthened specimens. Experimental results showed that the ultimate flexural capacity, deformation capacity, and energy dissipation capacity of strengthened RC pier columns were superior. Especially for strengthened specimens with low reinforcement ratios or corrosion reinforcement, their seismic performance could rival than that of columns with standard reinforcement ratios, which showed the advantage of BFRP sheets in the seismic retrofitting of existing bridge piers.